1999
DOI: 10.1055/s-2007-971134
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Drop Jump Training Methods: Effects on Leg Extensor Strength Qualities and Jumping Performance

Abstract: The purpose of this study was to determine the effects of two drop jump (DJ) training methods on the strength qualities of the leg extensors and vertical jumping performance. Thirty-five males were allocated to either a control group or one of two training groups, required to perform 72-90 DJ per week for 6 weeks: DJ for maximum rebound height (DJ-H) or DJ for maximum height and minimum ground contact time (DJ-H/t). The subjects were tested before and after the training on leg extensor function for maximum str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
72
1
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(116 citation statements)
references
References 18 publications
(26 reference statements)
9
72
1
3
Order By: Relevance
“…2). This is in agreement with Young et al (1999) who showed that a 6 week plyometric program failed to improve jumping height. It could also be hypothesized that plane hopping could not load the muscles sufficiently enough to increase their strength capacity in such short training period.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…2). This is in agreement with Young et al (1999) who showed that a 6 week plyometric program failed to improve jumping height. It could also be hypothesized that plane hopping could not load the muscles sufficiently enough to increase their strength capacity in such short training period.…”
Section: Discussionsupporting
confidence: 92%
“…Even though the majority of studies have shown a positive effect on vertical jumping performance, research on the effectiveness of plyometric training is sometimes inconclusive (Markovic 2007). Some studies have shown that training (Thomas et al 2009;Luebbers et al 2003) consisting of counter movement jumps (CMJ) or drop jumps (DJ) increases jumping height (Gehri et al 1998), while others have failed to find significant adaptations (Chimera et al 2004;Young et al 1999), despite of alterations in lower limbs muscle activity (Chimera et al 2004). These inconclusive results may be attributed to several factors such as differences in training program characteristics and type of jumping exercises (Markovic 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Few studies have accomplished to prepubertal boys (Kotzamanidis, 2006;Lehance et al, 2006). The relevant studies have reported that plyometric exercises improve jumping power and running velocities (Fatouros et al, 2012;Young et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…The present study revealed non-significant changes of the optimal velocity. Considering the fact that volleyball training aimed at the improvement of players' force also enhances their power and jumping ability [18,19], the results obtained are satisfactory. It must, however, be kept in mind that a study of female volleyball players by Häkkine [10] revealed an increase in all measured parameters only until the completion of the first competitive period, after which a decrease was noted.…”
Section: Discussionmentioning
confidence: 92%